2020
DOI: 10.1080/2573234x.2020.1832866
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and demographic analysis of COVID-19 infections with respect to weather factors in Europe

Abstract: The main objective of this study is to investigate the relationship between the COVID-19 and the weather factors of the most populated and industrialised countries in Europe and propose the best mathematical model to forecast the daily number of COVID-19 cases. To find the relationship between the COVID-19 and the weather factors of absolute humidity and temperature in Spain, France, Italy, Germany, and the United Kingdom, we conducted a Poisson analysis. We also used the General Linear Neural Network (GRNN) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…Supposing unchanged daily average temperature, a 1% relative humidity increase is associated with 0.006, 0.001, 0.011 and -0.013 reduction in the log of daily new confirmed cases in South Africa, Morocco, Ethiopia and Tunisia, respectively. These findings are similar to those in Spain ( Gharoie Ahangar et al, 2020 ), the world ( Zhang et al, 2021 ), China ( Oliveiros et al, 2020 ), Australia ( Ward et al, 2020 ) and in Italy ( Gharoie Ahangar et al, 2020 ).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Supposing unchanged daily average temperature, a 1% relative humidity increase is associated with 0.006, 0.001, 0.011 and -0.013 reduction in the log of daily new confirmed cases in South Africa, Morocco, Ethiopia and Tunisia, respectively. These findings are similar to those in Spain ( Gharoie Ahangar et al, 2020 ), the world ( Zhang et al, 2021 ), China ( Oliveiros et al, 2020 ), Australia ( Ward et al, 2020 ) and in Italy ( Gharoie Ahangar et al, 2020 ).…”
Section: Discussionsupporting
confidence: 87%
“…Given that the relative humidity is maintained constant, a 1 °C increase in the average temperature is linked to a 0.110 decrease in the log number of new confirmed cases in Tunisia. These findings are comparable to those in Africa ( Adekunle et al, 2020 ), Saudi Arabia ( Alkhowailed et al, 2020 ), the United States ( Chien and Chen, 2020 ), Spain ( Gharoie Ahangar et al, 2020 ), and China ( Liu et al, 2020 ). As a result, making a specific derivation about the effect of temperature on the COVID-19 spread could be difficult.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Studies conducted in 2020 investigated the correlation between the weather or climate variables (e.g., temperature, humidity, wind speed, visibility, rain, and solar radiation) and the number of COVID‐19 cases. Several of these studies have concentrated on different cities and countries around the world, for example, the United States and Europe (Bukhari & Jameel, 2020 ; Gharoie Ahangar et al, 2020 ), Africa (Adekunle et al, 2020 ), Russia (Lasisi and Eluwole, 2021 ), Wuhan, China (Ma et al, 2020 ), 122 cities in China (Xie & Zhu, 2020 ), India (Awasthi et al, 2020 ; Borah et al, 2020 ; Gupta, Pradhan, et al, 2020 ), Jakarta, Indonesia (Tosepu et al, 2020 ), Pakistan (Aslam et al, 2020 ), Brazil (Aule et al, 2020 ; Pequeno et al, 2020 ), Iran (Ahmadi et al, 2020 ). Preliminary studies that found no relationship between COVID‐19 transmission and atmospheric variables (e.g., temperature) were performed by Xie and Zhu ( 2020 ), Gupta, Raghuwanshi, et al ( 2020 ), and Yao et al ( 2020 ).…”
Section: Environmental Variables and Transmission Of Sars‐cov‐2 Pandemicmentioning
confidence: 99%